Решите ( с объяснением, если можно): ( ответ: )

сонька2005бедовая сонька2005бедовая    3   02.07.2019 00:10    1

Ответы
amira061 amira061  02.10.2020 17:59
Sin(2π/3 -x/4)*cos(π/6+x/4)*sinx/4 = 1/2 *(sin(2π/3 - x/4 +π/6+x/4) +
+sin(2π/3 - x/4 -π/6-x/4) ) *sinx/4 = 1/2 * (sin5π/6 + sin(π/2 -x/2)) *sinx/4  =
 1/2 * (1/2 + cosx/2) *sinx/4  =(1/4)*sinx/4  +1/2*sinx/4*cosx/2 = 
(1/4)*sinx/4  +(1/4)*( sin(x/4 -x/2) +cos(x/4 +x/2) ) =
(1/4)*sinx/4  +(1/4)* sin( -x/4) +(1/4)*cos3x/4 =(1/4)*sinx/4  -(1/4)* sinx/4 +
+(1/4)*cos3x/4= (1/4)*cos3x/4.

* * * * * * * * * * * * * * * * * * * * * * * * * *
использованы формулы : sin(π/2 -α) =cosα и
sinα*cosβ =(sin(α+β) + sin(α-β))/2 .
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра